State of the UK Climate in 2024 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2025)

State of the UK Climate 2023 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2024)

State of the UK Climate 2021 - Mike Kendon; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Tim Sparks; Judith Garforth; John Kennedy (International Journal of Climatology, 2022)
INTRODUCTION This report provides a summary of the UK weather and climate through the calendar year 2021, alongside the historical context for a number of essential climate variables. This is the eighth in a series of annual “State of the UK Climate” publications and an update to the 2020 report (Kendon et al ., 2021). It provides an accessible, authoritative and up‐to‐date assessment of UK climate trends, variations and extremes based on the most up‐to‐date observational datasets of climate quality. The majority of this report is based on observations of temperature, precipitation, sunshine and wind speed from the UK land weather station network as managed by the Met Office and a number of key partners and co‐operating volunteers. The observations are carefully managed such that they conform to current best‐practice observational standards as defined by the World Meteorological Organization (WMO). The observations also pass through a range of quality assurance procedures at the Met Office before application for climate monitoring. Time series of near‐coast sea‐surface temperature and sea level are also presented and in addition there is a short section on phenology which provides dates of “first leaf” and “bare tree” indicators for four common shrub or tree species. The reliance of this report on these observations highlights the ongoing need to adequately maintain the observation networks, in particular the UK land weather station network, into the future, to ensure that this UK climate monitoring capability is continued. National and regional statistics in this report are from the HadUK‐Grid dataset which is the principal source of data (Hollis et al ., 2019). Temperature and rainfall series from this dataset extend back to 1884 and 1836, respectively. Details of the datasets used throughout this report and how the various series which are presented are derived are provided in the appendices. A recent development to the underpinning dataset has been the inclusion of several million recently digitized historical monthly rainfall data (Hawkins et al ., 2022). These data significantly improve the geographical representation of rainfall before 1960 and allow for the extension of the national series back to 1836. The report presents summary statistics for the most recent year 2021 against the most recent decade 2012–2021, and following World Meteorological Organization (WMO) climatological best‐practice against the most recent 30‐year standard climate normal period 1991–2020 and the baseline period 1961–1990 (WMO, 2017). These two 30‐year reference periods do not overlap. The full series provide longer‐term context, while a comparison is also made to centennial averages for the Central England Temperature series. The decade 2012–2021 is a nonstandard reference period, but it provides a 10‐year “snapshot” of the most recent experience of the UK's climate and how that compares to historical records. This means that differences between 2012–2021 and the 30‐year reference periods may reflect shorter‐term decadal variations as well as long‐term trends. For this annual publication, the most recent decade (currently 2012–2021) changes every year, while the most recent 30‐year reference period changes every decade. For this year's report, we use the 30‐year reference period 1991–2020 for the first time, updated from 1981 to 2010 for last year's report (Kendon et al ., 2021). The baseline reference period 1961–1990 is retained, as this is a consistent reference period used not only throughout the series of State of UK Climate reports but also more widely for historical comparison, climate change monitoring and climate modelling following the WMO best‐practice. Throughout the report's text the terms “above normal,” “above average,” etc. refer to the 1991–2020 reference period unless otherwise stated. The majority of maps in this report show the year 2021 relative to the 1991–2020 reference period, that is, they are anomaly maps which show the spatial variation in this difference from average. Maps of actual values are in most cases not displayed because these are dominated by the underlying climatology, which for this report is of a lesser interest than the year‐to‐year variability. These data are presented to show what has happened in recent years, not necessarily what is expected to happen in a changing climate. Values quoted in tables throughout this report are rounded, but where the difference between two such values is quoted in the text (e.g., comparing the most recent decade with 1991–2020), this difference is calculated from the original unrounded values. Updates compared to state of UK climate 2020 The most recent 30‐year reference period is changed from 1981–2010 to 1991–2020. The dataset used to generate the summer North Atlantic Oscillation index is changed. Figures showing the UK average daily mean temperature and daily rainfall for each day of the year are added. A figure showing UK annual mean wind speed from 1969 has been added. The sea‐level section has been revised. Feedback We would welcome suggestions or recommendations for future annual publications of this report. Please send any feedback to the Met Office at ncic@metoffice.gov.uk . This State of the UK Climate report was supported by the Met Office Hadley Centre Climate Programme funded by BEIS and Defra.

State of the UK Climate 2020 - Mike Kendon; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Tim Sparks; Judith Garforth (International Journal of Climatology, 2021)
INTRODUCTION This report provides a summary of the UK weather and climate through the calendar year 2020, alongside the historical context for a number of essential climate variables. This is the seventh in a series of annual ‘State of the UK climate’ publications and an update to the 2019 report (Kendon et al ., 2020). It provides an accessible, authoritative and up‐to‐date assessment of UK climate trends, variations and extremes based on the most up to date observational datasets of climate quality. The majority of this report is based on observations of temperature, precipitation, sunshine and wind speed from the UK land weather station network as managed by the Met Office and a number of key partners and co‐operating volunteers. The observations are carefully managed such that they conform to current best practice observational standards as defined by the World Meteorological Organization (WMO). The observations also pass through a range of quality assurance procedures at the Met Office before application for climate monitoring. Time series of near‐coast sea‐surface temperature and sea‐level are also presented and in addition a short section on phenology which provides dates of first leaf and bare tree indicators for four common shrub or tree species. National and regional statistics in this report are from the HadUK‐Grid dataset which is the principal source of data (Hollis et al ., 2019). Temperature and rainfall series from this dataset extend back to 1884 and 1862, respectively. Details of the datasets used throughout this report and how the various series which are presented are derived are provided in the appendices. The report presents summary statistics for the most recent year 2020 against the most recent decade 2011–2020, the most recent 30‐year reference period (1981–2010) and the climate reference period 1961–1990. The full series provide longer‐term context, while a comparison is also made to centennial averages for the Central England Temperature series. The decade 2011–2020 is a non‐standard reference period, but it provides a 10‐year ‘snapshot’ of the most recent experience of the UK's climate and how that compares to historical records. This means differences between 2011 and 2020 and 30‐year reference periods may reflect shorter‐term decadal variations as well as long‐term trends. For this annual publication, the most recent decade (currently 2011–2020) changes every year, while the most recent 30‐year reference period (currently 1981–2010) changes every decade. For next year's report, the most recent 30‐year reference period will change from 1981–2010 to 1991–2020, while the climate reference period 1961–1990 will be retained. However, this report also includes a brief summary of key differences between preliminary 1991–2020 and 1981–2010 averages for temperature and rainfall. Throughout the report's text the terms “above normal” and “above average” and so on refer to the 1981–2010 baseline reference period unless otherwise stated. The majority of maps in this report show the year 2020 relative to the 1981–2010 reference period—that is, they are anomaly maps which show the spatial variation in this difference from average. Maps of actual values are in most cases not displayed because these are dominated by the underlying climatology, which for this report is of a lesser interest than the year‐to‐year variability. These data are presented to show what has happened in recent years, not necessarily what is expected to happen in a changing climate. Values quoted in tables throughout this report are rounded, but where the difference between two such values is quoted in the text (e.g., comparing the most recent decade with 1981–2010), this difference is calculated from the original unrounded values. Updates Compared to State of UK Climate 2019 A chart showing global surface temperature has been added. The section on sea level rise has been revised. A section summarizing key differences between preliminary 1991–2010 and 1981–2010 averages has been added. Feedback We would welcome suggestions or recommendations for future annual publications of this report. Please send any feedback to the Met Office at ncic@metoffice.gov.uk This State of the UK Climate report was supported by the Met Office Hadley Centre Climate Programme funded by BEIS and Defra.

State of the UK Climate 2019 - Mike Kendon; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Tim Sparks; Judith Garforth (International Journal of Climatology, 2020)
INTRODUCTION This report provides a summary of the UK weather and climate through the calendar year 2019, alongside the historical context for a number of essential climate variables. This is the sixth in a series of annual ‘State of the UK Climate’ publications and an update to the 2018 report (Kendon et al ., 2019). It provides an accessible, authoritative and up‐to‐date assessment of UK climate trends, variations and extremes based on the most up to date observational datasets of climate quality. The majority of this report is based on observations of temperature, precipitation, sunshine and wind speed from the UK land weather station network as managed by the Met Office and a number of key partners and co‐operating volunteers. The observations are carefully managed such that they conform to current best practice observational standards as defined by the World Meteorological Organization (WMO). The observations also pass through a range of quality assurance procedures at the Met Office before application for climate monitoring. Time series of near‐coast sea‐surface temperature (SST) and sea‐level are also presented and in addition a short section on phenology which provides dates of first leaf and bare tree indicators for four common shrub or tree species. National and regional statistics in this report are from the HadUK‐Grid dataset (Hollis et al ., 2019). Temperature and rainfall series from this dataset extend back to 1884 and 1862, respectively. Details are provided in the relevant sections and appendices. The report presents summary statistics for the year 2019 and the most recent decade (2010–2019) relative to 1961–1990 and 1981–2010 averages. The period 2010–2019 is a non‐standard reference period, but it provides a 10‐year ‘snapshot’ of the most recent experience of the UK's climate and how that compares to historical records. This means differences between 2010 and 2019 and the baseline reference averages may reflect shorter‐term decadal variations as well as long‐term trends. These data are presented to show what has happened in recent years, not necessarily what is expected to happen in a changing climate. The majority of maps in this report show the year 2019 relative to the 1981–2010 baseline reference averaging period—that is, they are anomaly maps which show the spatial variation in this difference from average. Maps of actual values are in most cases not displayed because these are dominated by the underlying climatology, which for this report is of a lesser interest than the year‐to‐year variability. Throughout the report's text the terms ‘above normal’ and ‘above average’, and so on refer to the 1981–2010 baseline reference averaging period unless otherwise stated. Values quoted in tables throughout this report are rounded, but where the difference between two such values is quoted in the text (e.g., comparing the most recent decade with 1981–2010), this difference is calculated from the original unrounded values. Updates compared to State of UK Climate 2018 A section on phenology has been added The method used to calculate rainfall percentiles (fig. 31) has been revised Updated climate data to HadUK‐Grid version 1.0.2.0, including data rescue projects that have improved or extended early monthly sunshine and rainfall series. Feedback We would welcome suggestions or recommendations for future publications of this report. Please send any feedback to the Met Office at ncic@metoffice.gov.uk This State of the UK Climate report was supported by the Met Office Hadley Centre Climate Programme funded by BEIS and Defra.